(untitled) (Journal of Atomic and Molecular Sciences, 2018)
It is necessary to fully understand the interaction between the cell penetration peptide and the different types of phospholipid membranes. In this research the interaction between R9 antibacterial peptide and asymmetric phospholipid is studied by using the method of coarse-grained dynamic simulation. The investigation shows that when there is only one R9 antibacterial peptide in the system, it is hard to penetrate through the phospholipid membrane spontaneously. When the concentration of the antibacterial peptide reaches a certain value, with the help of the enhanced electrostatic interactions and the cooperative effect, the peptides will pass through the phospholipid bilayer and reach the inside of the cell. Increasing the concentration of antimicrobial peptides is helpful to improve the penetration rate of the peptides. Our results can provide some theoretical guidance for drug delivery in the biological system.